Hydroxy-α sanshool induces colonic motor activity in rat proximal colon: a possible involvement of KCNK9 - Kubota, Kunitsugu (Am J Physiol Gastrointest Liver Physiol, 2015)
Various colonic motor activities are thought to mediate propulsion and mixing/absorption of colonic content. The Japanese traditional medicine daikenchuto (TU-100), which is widely used for postoperative ileus in Japan, accelerates colonic emptying in healthy humans. Hydroxy-α sanshool (HAS), a readily absorbable active ingredient of TU-100 and a KCNK3/KCNK9/KCNK18 blocker as well as TRPV1/TRPA1 agonist, has been investigated for its effects on colonic motility. Motility was evaluated by intraluminal pressure and video imaging of rat proximal colons in an organ bath. Distribution of KCNKs was investigated by RT-PCR, in situ hybridization, and immunohistochemistry. Current and membrane potential were evaluated with use of recombinant KCNK3- or KCNK9-expressing Xenopus oocytes and Chinese hamster ovary cells. Defecation frequency in rats was measured. HAS dose dependently induced strong propulsive “squeezing” motility, presumably as long-distance contraction (LDC). TRPV1/TRPA1 agonists induced different motility patterns. The effect of HAS was unaltered by TRPV1/TRPA1 antagonists and desensitization. Lidocaine (a nonselective KCNK blocker) and hydroxy-β sanshool (a geometrical isomer of HAS and KCNK3 blocker) also induced colonic motility as a rhythmic propagating ripple (RPR) and a LDC-like motion, respectively. HAS-induced “LDC,” but not lidocaine-induced “RPR,” was abrogated by a neuroleptic agent tetrodotoxin. KCNK3 and KCNK9 were located mainly in longitudinal smooth muscle cells and in neural cells in the myenteric plexus, respectively. Administration of HAS or TU-100 increased defecation frequency in normal and laparotomy rats. HAS may evoke strong LDC possibly via blockage of the neural KCNK9 channel in the colonic myenteric plexus.